2009
DOI: 10.1002/humu.20955
|View full text |Cite
|
Sign up to set email alerts
|

GermlineBRAFmutations in Noonan, LEOPARD, and cardiofaciocutaneous syndromes: Molecular diversity and associated phenotypic spectrum

Abstract: Noonan, LEOPARD and cardiofaciocutaneous syndromes (NS, LS and CFCS) are developmental disorders with overlapping features including distinctive facial dysmorphia, reduced growth, cardiac defects, skeletal and ectodermal anomalies, and variable cognitive deficits. Dysregulated RAS-mitogen-activated protein kinase (MAPK) signal traffic has been established to represent the molecular pathogenic cause underlying these conditions. To investigate the phenotypic spectrum and molecular diversity of germline mutations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
220
1
12

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(244 citation statements)
references
References 51 publications
10
220
1
12
Order By: Relevance
“…Pulmonic stenosis is commonly observed among individuals with mutations in the PTPN11 allele (18). Recently, studies using several mutant mice lacking HB-EGF expression have revealed that HB-EGF, in conjunction with ErbB receptors, has a critical role in normal cardiac valve formation at both cushion formation and tissue remodeling stages (37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pulmonic stenosis is commonly observed among individuals with mutations in the PTPN11 allele (18). Recently, studies using several mutant mice lacking HB-EGF expression have revealed that HB-EGF, in conjunction with ErbB receptors, has a critical role in normal cardiac valve formation at both cushion formation and tissue remodeling stages (37).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, although common clinical features were found in NS patients with different genetic mutations, substantial phenotypic variations were observed. For instance, pulmonic stenosis is more commonly observed among individuals with mutations in the PTPN11 allele, whereas hypertrophic cardiomyopathy is more closely associated with RAF1 mutations (18,19). These clinical observations suggested that multiple genetic factors contribute to the various phenotypes of NS and/or JMML.…”
mentioning
confidence: 99%
“…On a related note, some studies have found that, occasionally, mutations in BRAF and MEK1 can result in a phenotype more similar to NS or NSML than to typical CFC (Nystrom et al 2008;Nishi et al 2015;Sarkozy et al 2009). This finding has resulted in some debate regarding whether these individuals can be diagnosed as having a Noonan-like syndrome or whether they simply exhibit a milder phenotype of CFC (Neri et al 2008).…”
Section: Relationship Between Genotype and Neurocognitive Outcomesmentioning
confidence: 98%
“…Oxidation rates of [U-14 C]malate were measured in the presence of malonate (inhibitor of SDH) to prevent the oxidation of [2,[3][4][5][6][7][8][9][10][11][12][13][14] C]malate to proceed beyond one TCA cycle. ATP production was measured in incubations containing pyruvate, malate, creatine and ADP, in both the absence and presence (blank reaction) of arsenite.…”
Section: Biochemical Analysis In Blood Fibroblasts and Urinementioning
confidence: 99%
“…All molecules regulate the Ras-MAPK cascade. 2 Mitochondrial dysfunction is the most common inborn error of metabolism in children, the diagnosis of which is based on characteristic clinical symptoms of multisystem involvement and on the presence of metabolic markers. Clinical diagnosis is possible using a validated scoring system (mitochondrial disease criteria, MDC score) considering clinical signs and symptoms, as well as biochemical abnormalities (eg, lactic acidemia, elevated serum alanine and urinary excretion of certain organic acids and Krebs' cycle intermediates).…”
Section: Introductionmentioning
confidence: 99%